Costs of integrating hypertension care into HIV care in rural East African clinics. (1st May 2021) - Shade, Starley B.; Osmand, Thomas; Kwarisiima, Dalsone; Brown, Lillian B.; Luo, Alex; Mwebaza, Betty; Mwesigye, Aine Ronald; Kwizera, Enos; Imukeka, Haawa; Mwanga, Florence; Ayieko, James; Owaraganise, Asiphas; et al.
Abstract : Objective: Sub-Saharan Africa faces twin epidemics of HIV and noncommunicable diseases including hypertension. Integrating hypertension care into chronic HIV care is a global priority, but cost estimates are lacking. In the SEARCH Study, we performed population-level HIV/hypertension testing, and offered integrated streamlined chronic care. Here, we estimate costs for integrated hypertension/HIV care for HIV-positive individuals, and costs for hypertension care for HIV-negative individuals in the same clinics. Design: Microcosting analysis of healthcare expenditures within Ugandan HIV clinics. Methods: SEARCH (NCT: 01864603) conducted community health campaigns for diagnosis and linkage to care for both HIV and hypertension. HIV-positive patients received hypertension/HIV care jointly including blood pressure monitoring and medications; HIV-negative patients received hypertension care at the same clinics. Within 10 Ugandan study communities during 2015–2016, we estimated incremental annual per-patient hypertension care costs using micro-costing techniques, time-and-motion personnel studies, and administrative/clinical records review. Results: Overall, 70 HIV-positive and 2355 HIV-negative participants received hypertension care. For HIV-positive participants, average incremental cost of hypertension care was $6.29 per person per year, a 2.1% marginal increase over prior estimates for HIV care alone. For HIV-negative participants, hypertension care cost $11.39 per person per year, a 3.8% marginal increase over HIV care costs. Key costs for HIV-positive patients included hypertension medications ($6.19 per patient per year; 98% of total) and laboratory testing ($0.10 per patient per year; 2%). Key costs for HIV-negative patients included medications ($5.09 per patient per year; 45%) and clinic staff salaries ($3.66 per patient per year; 32%). Conclusion: For only 2–4% estimated additional costs, hypertension care was added to HIV care, and also expanded to all HIV-negative patients in prototypic Ugandan clinics, demonstrating substantial synergy. Our results should encourage accelerated scale-up of hypertension care into existing clinics. Abstract : Supplemental Digital Content is available in the text